Quantum mechanical study of YTiO3 to the investigation of piezoelectricity - Ciríaco Pinheiro, José; Dirceu de Paula Ferreira, Raimundo; Antonio Barros Dos Santos, Marcos; Da Silva Lobato, Maycon; Pinto Barbosa, Jardel; De Souza Farias, Marcio; Florncio de Figueiredo, Antonio; Treu-Filho, Oswaldo [UNESP]; Toshiaki Kondo, Rogério (Hindawi, 2011)
In previous articles we reported through theoretical studies the piezoelectric effect in BaTiO3, SmTiO3, and YFeO3. In this paper, we used the Douglas-Kroll-Hess (DKH) second-order scalar relativistic method to investigate the piezoelectricity in YTiO3. In the calculations we used the [6s4p] and [10s5p4d] Gaussian basis sets for the O (3P) and Ti (5S) atoms, respectively, from the literature in combination with the (30s21p16d)/[15s9p6d] basis set for the Y ( 3D) atom, obtained by generator coordinate Hartree-Fock (GCHF) method, and they had their quality evaluated using calculations of total energy and orbital energies (HOMO and HOMO-1) of the 2TiO+1 and 1YO+1 fragments. The dipole moment, the total energy, and the total atomic charges in YTiO3 in C s space group were calculated. When we analyze those properties we verify that it is reasonable to believe that YTiO3 does not present piezoelectric properties. Copyright © 2011 Raimundo Dirceu de Paula Ferreira et al.